Model Desain Taman Toga Desa Bukian, Kecamatan Payangan, Kabupaten Gianyar - Kadek, Wiranatha; Dharmadiatmika, I Made Agus; Krisnandika, Anak Agung Keswari (Jurnal Lanskap Indonesia, 2021)
Physic Garden (Toga) is described as lot of soil in house yards which is utilized as a place to grow medicinal plants to be consumed by a family. The functional value of Toga garden in Bukian Village’s yards have been accomplished, however, the arrangement of the garden does not consider the plants’ characteristics, aesthetics, as well as the philosophy of Balinese Traditional Garden. The basic concept applied is a thematic garden which balances between the beauty of garden and the supply of medicinal plants based on Balinese Traditional Garden philosophy which consists of 7 factors of Balinese garden formation. This concept points out the physical space as the base, roof, wall, and design pattern in each mandala that are related to one another as a unity, therefore it can be a guide for the house owner in arranging the garden, as well as recommending design models of Toga garden from the placement of the plants in physical space that has been designed based on the characters of each plants and makes Balinese traditional garden philosophy as the guide. Every garden design in house yards is expected to use Balinese traditional philosophy as the base in order to maintain and preserve the local culture, as well as keeping the health of the family with herbal medication